A Regional Perspective on Canadian Suburbanization: Reflections on Richard Harris's Creeping Conformity - McCann, Larry (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2006)
Richard Harris's recently published Creeping Conformity offers a carefully reasoned interpretation of the country's evolving suburban landscape from the late-nineteenth to the mid-twentieth century. In particular, Harris argues that Canadian suburbs have passed from a state of diversity to one of conformity. No longer are suburbs a jumble of land uses and social classes. Instead, through the initiative of large, vertically integrated corporations, supported by federal mortgage and other fiscal policies, suburbs have become more middle class, yielding to a “conformity” in the shaping of their physical design and social make-up. This paper suggests that factors of a distinctive regional character—for example, corporate land development in western Canadian cities before World War I and provincial town planning and zoning legislation in the 1920s—require elaboration within the “diversity to conformity” model. Once done, we can then speak more assuredly about how, when, and to what extent “conformity” has emerged to distinguish Canada's suburban landscape.